2017
DOI: 10.1177/1525740117705117
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Language Development of Young Children With Autism: A Review of Research in Music

Abstract: Research demonstrates connections among children's music actions, their engagement abilities, and their language development. Although the link between music and the engagement abilities of young children with autism is well established, there is not enough evidence on the effectiveness of music strategies and music therapy interventions to promote language development of young children with autism. The purpose of this review is to examine and analyze current literature on the systematic use of music and music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 42 publications
0
9
0
4
Order By: Relevance
“…There are many studies on music as well as music therapy on individuals with autism, with successful outcomes. Most of the studies reported positive outcomes in the areas of social skills (Paul et al, 2015;Preis et al, 2016;Thompson, 2017;Vaiouli & Ogle, 2015), as well as language and communication skills (Mossler et al, 2017;Thompson, 2017;Vaiouli & Andreou, 2018). Nevertheless,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on music as well as music therapy on individuals with autism, with successful outcomes. Most of the studies reported positive outcomes in the areas of social skills (Paul et al, 2015;Preis et al, 2016;Thompson, 2017;Vaiouli & Ogle, 2015), as well as language and communication skills (Mossler et al, 2017;Thompson, 2017;Vaiouli & Andreou, 2018). Nevertheless,…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the preceding paragraphs, numerous studies on music as an intervention and music therapy for children with autism have reported positive effects in the aspects of social, communication and language skills (Mossler et al, 2017;Paul et al, 2015;Preis et al, 2016;Thompson, 2017;Vaiouli & Andreou, 2018;Vaiouli & Ogle, 2015). Most of these studies were conducted using qualitative approach.…”
Section: The Use Of Music For Children With Autismmentioning
confidence: 99%
“…Reviews of the impact of music on individuals with autistic spectrum disorder have generally shown positive outcomes including improved non verbal and verbal communication, motor development, coordination, body awareness, sensory perception, social emotional reciprocity and a wide range of social skills (Geretsegger et al, 2014;Janzen and Thaut, 2018;Shi et al, 2016;Srinivasan and Bhat 2013;Vaiouli and Andreou, 2018). In addition to the impact on these functions De Vries and colleagues (2015) showed that music reduced anxiety and improved cognitive skills, attention to task, enhanced body awareness, self care skills and the expression, recognition, understanding and processing of emotions.…”
Section: Schizophreniamentioning
confidence: 99%
“…Young children's competence in verbal expression is still developing. Music thus offers them a presymbolic way to focus their attention, express their intentions, and interact and communicate with others (Vaiouli & Andreou, 2018). Music is an age-appropriate, engaging medium that promotes preverbal communication among young children including eye contact, imitation, turn taking, and social gestures in addition to verbal communication; it is also effective for children with special educational needs (Vaiouli et al, 2018).…”
Section: Rhythm In Music As a Means Of Enhancing Attunement In Childr...mentioning
confidence: 99%